1991
DOI: 10.1111/j.1365-2559.1991.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian morphology in long‐term androgen‐treated female to male transsexuals. A human model for the study of polycystic ovarian syndrome?

Abstract: Descriptions of the effect of androgens on ovarian human tissues are exceptional. This opportunity was provided for us by 17 women with transsexualism--female to male transsexuals (TSX)--who had been given androgens for a mean period of 21 months before hystero-salpingo-oophorectomy took place. Twenty-nine ovaries from TSX and 14 control ovaries from 13 regularly cycling women were examined. As compared with controls, TSX ovaries were enlarged and displayed a two-fold increase in cystic follicles and a 3.5-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
1
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(99 citation statements)
references
References 25 publications
4
91
1
3
Order By: Relevance
“…Pathological conditions in humans that cause hyperandrogenism, for example, congenital adrenal hyperplasia (38) and studies in transsexual women treated with high doses of testosterone (39,40,41,42) show conflicting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological conditions in humans that cause hyperandrogenism, for example, congenital adrenal hyperplasia (38) and studies in transsexual women treated with high doses of testosterone (39,40,41,42) show conflicting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] In particular, polycystic ovaries have been demonstrated in female to male transsexuals receiving long-term androgen treatment. [51][52][53] The underlying basis for androgen-induced follicle formation in non-human primates has been explored in studies that demonstrated increased ovarian size and follicle number following subcutaneous placement of silastic capsules containing testosterone. 54 Compared with adult women, there are relatively few comprehensive studies of polycystic ovary morphology in adolescent girls.…”
Section: Ovarian Morphologymentioning
confidence: 99%
“…Androgens induce male sexual differentiation before birth, promote sexual maturation during puberty, and maintain male reproductive function in adults (1). In women, androgens serve as precursors for estrogen biosynthesis (2) while also playing significant roles in normal as well as pathologic ovarian development (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%